Persepsi Bakal Guru Pendidikan Khas terhadap Pendidikan Khas di Malaysia - Nurul Hidayah Liew Abdullah; Siti Fatimah Mohd Jamil; Marina Ibrahim Mukthar; Maziana Mohamed; Aini Nazura Paimin (USIM Press, 2024)
Vol. 6 No. 1 (2021): Jurnal Sains Insani